Particles in different indoor microenvironments-its implications on occupants. (September 2016) - Massey, David D.; Habil, Mahima; Taneja, Ajay
Abstract: Changes over recent decades in outdoor concentrations of air pollutants are well documented. However, the impacts of air pollution on an individual's health actually relate not to these outdoor concentrations, but to their personal environment in indoors where they spend most of their time. For this a campainage study was conducted in three different microenvironments, i.e., offices, shops and commercial centers; for each site, we choose two different locations to examine the coarse particles (PM10 & PM5.0 ) and fine particles (PM2.5, PM1.0, PM0.5 & PM0.25 ) concentrations which varied from 288 to 327 μg m -3 for PM10, 201.58–272.98 for PM5.0, 185.68–227.44 for PM2.5, 105.85–139.17 for PM1.0, 52.78–101.33 for PM0.5 and 36.48–56.13 for PM0.25 . Metal concentration of Zn, Pb, Ni, Fe, Cr, Cd, Mg and Cu in PM2.5 and for their related health effects have also been analysed. The concentration values of heavy metals in PM2.5 were measured using Atomic Absorption spectrophotometry. The exposure factor and health risk assessment for carcinogenic effects due to heavy metal contaminants like (Cr, Cd, Ni and Pb) have been calculated for adults working in different indoor environment by following the methodology prescribed by US EPA. Ni had the highest Excess Cancer Risks followed by Cd and Cr in the different indoor environment. Three factors each in different indoor environment have been identified using Positive Matrix Factorization. The campainage study was carried from September 2011 to December 2011. Highlights: PM concentrations were found 2.8 to 9 times higher from the WHO and NAAQS standards. The PM concentrations were found highest in the offices followed by shops and commercial centers. Source apportionment was done to know the probable sources of pollutants. Risk assessment from carcinogenic metals was carried out.